Meu mar - Bucuane, Juvenal (Editora do Carmo, 2018)
Keywords: digte

Meu mar - Bucuane, Juvenal (Poesia / Filhos do vento, 2019)
Keywords: 2000-2099; 21st century; Mozambican poetry (Portuguese); Mozambique; Poetry; Poésie; poetry; poetry (form)

Crendice ou crença: quando os manes ancestrais se tornam deuses - Bucuane, Juvenal (Prosa (Alcance Editores), 2012)
A novel

Arresto de vozes: ou o cúmulo discursivo literário - Bucuane, Juvenal (Cronicas, 2017)
Keywords: African literature (Portuguese); African literature (Portuguese) Black authors History and criticism; Authors, Mozambican; Authors, Mozambican Criticism and interpretation; Black authors History and criticism; Bucuane, Juvenal, 1951- Criticism and interpretation; Criticism and interpretation; Criticism, interpretation, etc; Essais; Essay; Essays; History and criticism; Intellectual life; Littérature africaine (portugaise) Auteurs noirs Histoire et critique; Littérature mozambicaine (portugaise) Histoire et critique; Mozambican literature (Portuguese); Mozambican literature (Portuguese) History and criticism; Mozambique; Mozambique Intellectual life; essays; Écrivains mozambicains Critique et interprétation

Meu mar - Bucuane, Juvenal (Poesia, 2018)

O fundo pardo das coisas: poesia - Bucuane, Juvenal; Cuna, Aurélio (Poesia, 2014)
Keywords: Anthologie; Lyrik; Mozambican poetry (Portuguese); Moçambique; Poetry; Portugiesisch; Poésie; poetry

Detalhes de uma vida de silêncio - Baptista Júnior, Heliodoro; Bucuane, Juvenal (Poesia, 2017)